Reduced Prevalence of Cognitive impairment in families with exceptional longevity - Cosentino, Stephanie (2013)
OBJECTIVE: To determine if families with exceptional longevity are protected against cognitive impairment consistent with Alzheimer’s disease (AD). DESIGN: Cross-sectional analysis. SETTING: Multi-site study in NY, MA, PA, and Denmark. PARTICIPANTS: 1870 individuals (1510 family members and 360 spouse controls) recruited through the Long Life Family Study (LLFS). MAIN OUTCOME MEASURES: Prevalence of cognitive impairment based on a diagnostic algorithm validated using the National Alzheimer’s Coordinating Center dataset. RESULTS: The cognitive algorithm classified 546 (38.5%) individuals as having cognitive impairment consistent with AD. LLFS probands had a slightly but not statistically significant reduced risk of cognitive impairment compared with spouse controls (121/232 for probandsvs 45/103 for spouse controls: OR = 0.70; 95% CI (0.4–1.4)), whereas LLFS sons and daughters had a clearly reduced risk of cognitive impairment (11/213 for sons and daughters vs 28/216 for spouse controls: OR = 0.40; 95% CI (0.2–0.9)). Restriction to nieces and nephews in the offspring generation attenuated this effect (37/328 for nieces and nephews vs 28/216 for spouse controls OR = 0.70; 95% CI (0.4–1.4). CONCLUSIONS: Rates of cognitive impairment characteristic of AD were relatively high. In the proband generation, rates were comparable across family members and spouse controls whereas sons and daughters of probands had significantly lower rates than spouse controls. Results suggest a delayed onset of cognitive impairment in families with exceptional longevity, but assessment of age-specific incidence rates is required to confirm this hypothesis.